2015
DOI: 10.1007/s00464-015-4115-z
|View full text |Cite
|
Sign up to set email alerts
|

Do height and weight affect the feasibility of single-incision laparoscopic cholecystectomy?

Abstract: Preoperative identification of the factors increasing the risk of conversion may assist surgeons in making decisions concerning the management of patients, including appropriate use of SILC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…However, there seems to be varying degrees of difficulty in individual cases. In previous studies, height and BMI were reported as predictive factors for difficult SILC cases , with patients with a higher BMI or taller height had longer operative times. These effects are believed to be due to the longer distance to the target organ .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there seems to be varying degrees of difficulty in individual cases. In previous studies, height and BMI were reported as predictive factors for difficult SILC cases , with patients with a higher BMI or taller height had longer operative times. These effects are believed to be due to the longer distance to the target organ .…”
Section: Discussionmentioning
confidence: 93%
“…Previous papers have reported that BMI and height are predictive factors for prolonged operative duration in SILC patients . BMI is also associated with prolonged operative duration in CLC .…”
Section: Introductionmentioning
confidence: 91%
“…Since Navarra et al [ 3 ] reported SILC in 1997, various multilumen ports that allow simultaneous multiple instrument insertion including the SILS port, ASC Triport (Advanced Surgical Concept, Wicklow, Ireland) and the GelPOINT device, angled or flexible scopes, articulated instruments and instruments of variable length have been introduced [ 4 5 11 ]. Son et al [ 6 ] used a hand-made port for SILC using the ALEXIS wound retractor (Applied Medical) and sterile surgical gloves.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that the distance between umbilical port and the GB increases with height and obesity [ 14 ]. Consequently, it is more difficult to place the scope and grasper near to the operative field, leading to more struggle and longer operations [ 4 ]. In this study, SILC was very difficult when the distance between umbilicus and rib costal margin was more than 17 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation